Knowledge, Attitude and Practices Regarding Third Wave of Coronavirus Pandemic among the Community People in Kathmandu Valley, Nepal - Pasa, Rajan Binayek; Khatri, Bishnu Bahadur; Khanal, Shanti Prasad; Teijlingen, Edwin van; Adhikari, Devendra (Nepal Journal of Multidisciplinary Research, 2024)
Background: Coronavirus pandemic (COVID-19) is a massive global health crisis. This paper aims to describe knowledge, attitude and practices (KAP) regarding Coronavirus pandemic among the community people residing in Kathmandu Valley. Methods: We have applied cross-sectional study design in which required data were collected from 312 sample households using accidental sampling procedure. We applied self-administered hand given questionnaire (Cronbach's alpha 0.97) consisting 105 items variables (35 each for KAP) on a six-point Likert scale, from 0(not applicable) to 5(strongly agree). Results: The study found that summative values of attitude (x̄ 3.71-3.97) and practices (x̄ 3.70-4.12) found comparatively weaker than knowledge (x̄ 3.09-4.24). About 124(39.7%) respondents have associated comorbidities allied with social distancing, masking/globing behavior, hand washing and sanitizing, physical exercise, PCR test/vaccination, health seeking behavior. KAP index is largely defined by variable family monthly expenditure on food/vegetable and their KAP index was significantly higher than others. However, presence of family members suffered from COVID-19 has negatively contributed to the KAP index. Conclusion: The denser views on KAP are the consistently with closer to agree and strongly agree points. KAP index found significant but skewed to left for Kirtipur and skewed to right for Lalitpur and Suryabinayak. Novelty: The municipal governments have been offering efficient and dedicated health services to the community people. However, knowledge, attitude and practices among the community people of residing in Kathmandu, Bhaktapur and Lalitpur found different. Therefore, the results of the study are valuable to policy makers and planners especially in the areas of healthcare and public health during pandemics.